Examine the level of customer satisfaction towards service quality provided by SOCSO Melaka / Norsham Azeanti Mat Zaki - Mat Zaki, Norsham Azeanti (2009)
Customer satisfaction is the individual’s perception of the performance of the product or service in relation to his or her expectations. Every customer will have drastically different expectations. Basically, the concept of customer satisfaction is an expectation. A customer whose experiences fall below their expectations will be dissatisfied whereas if it matches with expectations will be satisfied and customers whose expectations are exceeded will be very satisfied or delighted. (Shiffman and Kanuk, 2004). At SOCSO Melaka, delivering the best service to their customer is the best reward for them in order to achieve their customer satisfaction towards the service that is provided by them. And that’s why SOCSO provides electronic simple messages system for their customer to comment, give some suggestion or any problems and anything that they are not satisfy with the service provided by SOCSO and this will be monitored by headquarters in Ampang, Kuala Lumpur named “e-aduan”. Achieving customer satisfaction is the primary goal for most service firms today (Jones and Sasser, 1995). Increasing customer satisfaction and customer retention leads to improve profits, positive word-of-mouth, and lower marketing expenditures (Reichheld,1996; Heskett et al., 1997) Service quality is an attitude formed by a long term, overall evaluations of a firm’s performance. It is because customer are evaluate the service quality from the own experience undergoing the services and it will impact overall evaluation of performance. Without doubt, the two concepts of customer satisfactions and service quality are intertwined. However, the relationships between these two concepts are unclear. Although measurement of customer satisfaction and service quality are both obtained by comparing perceptions to expectations, subtle differences between the two concepts are seen in their operational definitions. While satisfaction compares consumers perceptions to what consumers would normally expect, service quality that compares perception to what a consumer should expect from a firm that delivers high quality services (Hoffman and Bateson, 2006).